Vpliv zelene infrastrukture na povezanost prebivalcev z naravo v Lagosu - Dipeolu, Adedotun Ayodele (Urbani izziv, 2022)
The high rate of loss of urban green spaces is reducing connectivity between people and nature, and the ability of the urban population to appreciate and enjoy the natural environment. However, not much is known about the extent to which ongoing efforts at planning green infrastructure are influencing residents’ connectedness to nature, especially in cities in sub-Saharan Africa. This study investigates the influence of green infrastructure (GI) on residents’ self-perceived connectedness with nature in selected residential neighbourhoods in Lagos, Nigeria. Through a multi-stage sampling technique, 1,560 residents were included in a survey and the data were analysed using descriptive and categorical regression analyses. The results showed that, although the residents were generally dissatisfied with the quality and quantity of GI in their neighbourhoods, they felt that the existing GI has a significant positive influence on their connection to nature. The regression analysis also revealed that the current state and availability of green areas for relaxation in the neighbourhoods were the two GI characteristics with the most influence on residents’ sense of connectedness to nature. These findings are instructive in noting that, to improve the urban population’s connectedness to nature using GI, city planners and managers should pay specific attention to providing and maintaining green areas for relaxation in residential neighbourhoods in the study area and beyond.
Keywords: connectedness to nature; green infrastructure; Lagos; mestni prebivalci; neighbourhoods; povezanost z naravo; soseske; trajnostni razvoj mest; urban residents; zelena infrastruktura